Analisis Sudut Pandang Kamera Dan Jenis Kamera - Triyono Triyono; M. Ardy Hariwibowo; Bian Pramana Putra (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
The development of computer technology in particular fields of multimedia, visual and audio broadcasting already very rapidly growing at this time as well as the extent of the need for information on the society, the more recent contributions in presenting the image capture, the camera is the most popular tool in photography. The name is derived from the camera obscura, Latin for "dark room", an early mechanism for projecting a display where an indoor function like the workings of a modern photographic camera, except there is no way at this time to take down the display of the drawing in addition to manually follow in his footsteps. In the world of photography, a camera is a device to establish and record a shadow portraits on sheet film. At the television cameras, the system of lenses to form an image on a light sensitive plate. This plate will emit electrons into the target plate when exposed to light. Furthermore, a steady stream of electrons that are treated electronically. In the world of photography does little photographers especially that still seems to be beginners, on things that are technical, such as regulating the aperture diaphragm setting, pace, and distance settings. It's also possible, as long as it is not unthinkable that in the picture contained certain values that can make photos that are good or otherwise become a mess. One of them is setting the composition. May have never imagined, that by setting the actual composition can be highlighted the main subject. Not even rarely will support the success of the photos that we make. a core tool in photography called camera also has different types with masingmasing kegunaanya. With the development of technology, people can search for information using a cell phone so that it is able to be accessed anytime and anywhere.